O MOVIMENTO ESTUDANTIL UNIVERSITÁRIO NO BRASIL: ENTRE A LUTA PELA REFORMA UNIVERSITÁRIA E A RESISTÊNCIA À DITADURA (1960-1968) - FREITAS BRITO, ANTÔNIO MAURÍCIO (Universidad Nacional del Litoral, 2018)
The article discusses the performance of the university student movement in the 1960s. It presents the main mobilization patterns of the beginning of the decade, especially the struggle for university reform. It explores the repressive impact of the 1964 coup on the student movement. It demonstrates the support of university sectors to the fall of Goulart emphasizing the importance of research on anticommunist student organizations. It discusses the reorganization of a student action in opposition to the military regime having its apex in 1968. It underlines the government reaction inspired by the anticommunism and the repressive escalation until the edition of the Institutional Act no. 05. It raises some historiographic questions about the studentmovement in Brazil.